-.17x+0.2(x-2)=-0.27(1-x)

Simple and best practice solution for -.17x+0.2(x-2)=-0.27(1-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -.17x+0.2(x-2)=-0.27(1-x) equation:


Simplifying
-0.17x + 0.2(x + -2) = -0.27(1 + -1x)

Reorder the terms:
-0.17x + 0.2(-2 + x) = -0.27(1 + -1x)
-0.17x + (-2 * 0.2 + x * 0.2) = -0.27(1 + -1x)
-0.17x + (-0.4 + 0.2x) = -0.27(1 + -1x)

Reorder the terms:
-0.4 + -0.17x + 0.2x = -0.27(1 + -1x)

Combine like terms: -0.17x + 0.2x = 0.03x
-0.4 + 0.03x = -0.27(1 + -1x)
-0.4 + 0.03x = (1 * -0.27 + -1x * -0.27)
-0.4 + 0.03x = (-0.27 + 0.27x)

Solving
-0.4 + 0.03x = -0.27 + 0.27x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.27x' to each side of the equation.
-0.4 + 0.03x + -0.27x = -0.27 + 0.27x + -0.27x

Combine like terms: 0.03x + -0.27x = -0.24x
-0.4 + -0.24x = -0.27 + 0.27x + -0.27x

Combine like terms: 0.27x + -0.27x = 0.00
-0.4 + -0.24x = -0.27 + 0.00
-0.4 + -0.24x = -0.27

Add '0.4' to each side of the equation.
-0.4 + 0.4 + -0.24x = -0.27 + 0.4

Combine like terms: -0.4 + 0.4 = 0.0
0.0 + -0.24x = -0.27 + 0.4
-0.24x = -0.27 + 0.4

Combine like terms: -0.27 + 0.4 = 0.13
-0.24x = 0.13

Divide each side by '-0.24'.
x = -0.5416666667

Simplifying
x = -0.5416666667

See similar equations:

| 2x+-3(x+-1)=8 | | Y=10-1 | | 2n+1=-7+4n | | -12x-9=168 | | 3(5-5x)=-105 | | 6x-(x+3)=2 | | 9n+3n^2=176.75 | | x^4-7x^2+16=0 | | 3p+6=6-p | | 16(v+1)-4v=4(3v+1)-7 | | M+2m+-6=-12+2m | | y^2dx+(3xy+y^2-1)dy=0 | | A=5n-600 | | y=.5x-10 | | 4z+z+5=z | | -19=x+3(2x-4) | | -3x+15=2x-2 | | 31=s+2.5s+10 | | 10x^2-5=0 | | 2(12-4y)+4y=24 | | 7g-21=16 | | sqrt(x+21)-1=x | | 5f-3=32 | | 183=-w+87 | | X-26=12 | | 25m^2a^2-4a^2= | | 3(12)+y=36 | | 4.7m=18-2.7m | | 12k+50=40 | | 49x-16x^3=0 | | -2=(7y-8y)2+14 | | (9n+4)+(3n^2-0.75)=180 |

Equations solver categories